INDUSTRIAL POLICY OF REGIONS OF THE NORTH CAUCASIAN FEDERAL DISTRICT IN THE CONTEXT OF GEOECONOMIC CHALLENGES - Natalya Kiseleva (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 3, Èkonomika,Èkologiâ, 2018)
The article provides a short review of influence of geoeconomic restrictions on the economy and industrial policy of the Russian Federation. The authors mention the list of economically restricted companies with the indication of their industry affiliation. The characteristic of import dependence scales in key industries of the Russian economy is given. The mechanism of influence of geoeconomic restrictions on economic and social situation in Russia is shown on the example of the food market. It is proved that the agro-industrial complex couldn’t replenish the shortage at the domestic food market. The authors also point to strengths and weaknesses of import substitution policy in the economy and the social sphere of national economy. The main directions ofimport substitution policy in the Russian Federation are revealed with the indication of standard and legal documents, in which they are enshrined. The comparative analysis of import substitution plans of regions of the North Caucasian Federal District is carried out. The plans include such provisions as branch priorities, accounting of the developed branch structure of economy, strengths and weaknesses. From the authors’ viewpoint, the import substitution plans of the Republics of Dagestan, Karachay-Cherkess Republic, the Republic of Northern Ossetia, the Chechen Republic are the most developed, as they take into account branch structure and promote regional growth. In these documents the directions of further deepening of regional specialization of an access into the markets of other regions of Russia are proved. It is noted that there are measures of regional policy, which have been used within the last decades and have not proved their efficiency. The authors make a valid conclusion about the insufficient innovation of regional plans of import substitution in the North Caucasian Federal District that hinders development and search of a niche for each of the regions in the system of national and international division of labour.